Wnt2bb Induces Cardiomyocyte Proliferation in Zebrafish Hearts via the jnk1/c-jun/creb1 Pathway - Peng, Xiangwen; Fan, Shunyang; Tan, Jing; Zeng, Zhi; Su, Meiling; Zhang, Yuan; Yang, Ming; Xia, Luoxing; Fan, Xuejiao; Cai, Weibin; Tang, Wai Ho (Frontiers in Cell and Developmental Biology, 2020)
According to previous studies, inhibition of the canonical Wnt signaling pathway promotes regeneration of the zebrafish heart, and treatment of the injured heart tissue with the Wnt activator BIO impairs cardiomyocyte proliferation. However, the mechanism by which Wnt signaling regulates downstream gene expression following heart injury remains unknown. Here, inhibition of injury-induced myocardial wnt2bb and jnk1/creb1/c-jun signaling impairs heart repair after apex resection. The expression of jnk1, creb1 and c-jun is decreased in hearts expressing a dominant negative wnt2bb mutant and increased in hearts overexpressing wnt2bb after ventricular amputation. Overexpression of creb1 sufficiently rescues the dn-wnt2bb-induced phenotype of reduced nkx2.5 expression and attenuated heart regeneration. In addition, wnt2bb/jnk1/c-jun/creb1 signaling was increased in Tg(hsp:dkk1) transgenic fish, whereas it was decreased in Tg(hsp:wnt8) transgenic fish, indicating that canonical Wnt signaling and noncanonical Wnt signaling antagonize each other to regulate heart regeneration. Based on our findings, the wnt2bb-mediated jnk1/c-jun/creb1 noncanonical Wnt pathway regulates cardiomyocyte proliferation.